If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 54 + -4x = 23x + 24 Reorder the terms: 54 + -4x = 24 + 23x Solving 54 + -4x = 24 + 23x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23x' to each side of the equation. 54 + -4x + -23x = 24 + 23x + -23x Combine like terms: -4x + -23x = -27x 54 + -27x = 24 + 23x + -23x Combine like terms: 23x + -23x = 0 54 + -27x = 24 + 0 54 + -27x = 24 Add '-54' to each side of the equation. 54 + -54 + -27x = 24 + -54 Combine like terms: 54 + -54 = 0 0 + -27x = 24 + -54 -27x = 24 + -54 Combine like terms: 24 + -54 = -30 -27x = -30 Divide each side by '-27'. x = 1.111111111 Simplifying x = 1.111111111
| -103-7x=10+16 | | 6x+13=147-10x | | 6x+13=147-10 | | 2v^2+7v=-5 | | t+1+2+3+4+5+6+7+8+9=123456789 | | 114-6x=9x+4 | | 3x+9x+6x=396x | | -3x+(7ab-4)-5x-3b-(3a+22a-x)= | | 132-5x=31x+20 | | 13-8x=213-43x | | 2k+3= | | 41=15+13(9m-16) | | 41=15+13(19m-16) | | 2a+3=2a+4 | | log(x-2)+log(2-x)=1 | | 3lnx+ln(9-(8x^3))=0 | | 210S+265E=4485 | | 3lnx+ln(9-8x^3)=0 | | 3o+13=23-2o | | 15-(2x+3)=3-3X | | 23-3x=6x+19 | | 10-8x=67-29x | | - 4(X-2)-3(x+1)=6-2X | | 9x-6=0 | | 81x^2=26 | | -6x-5=-10x+19 | | 14x^2-11x+15=0 | | 4/9x=-8/15 | | 2p+20-p/6=p/4+1 | | 2a+2=4a-8 | | x^2+4x-2x-8=16 | | (w^2-2w-3)/(3w^2-27) |